The Limits and Opportunities of Practising Journalism in the Digital Space: A Gender Perspective - Alexandra Codău; Valentin Vanghelescu (Gender a Výzkum)
This study explores the professional debut of women journalists in the digital environment in Romania, focusing on the dynamics of gender identity. The research examines the phenomenon of the viralisation of the ﬁrst material published by a young journalist and the subsequent online reactions to it on social media. The case study method is used to analyse the discursive and institutional consequences of this event, observing the reactions of various stakeholders (the author, readers, journalists, NGOs, and the academic community). The ﬁndings highlight the opportunities created by the viral nature of the debut article, which provides the journalist with a discursive platform post-publication to address gender-related issues and enhances her visibility. However, the analysis also exposes signiﬁcant challenges faced by the journalist, such as sexist and misogynistic discourse in the comments on social media, demonstrating that in the public sphere of Romania, a woman journalist's online debut is viewed and analysed not just in terms of professional standards but also from a gender perspective.